Profil Pemecahan Masalah Geometri Berdasarkan Tahapan Wallas Ditinjau dari Adversity Quotient - Imam Saifuddin (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2018)
This study aims to provide a description of the symptoms, phenomena, or facts regarding geometric problem solving based on the stages of Wallas in terms of Adversity Quotient. This research is a descriptive study with a qualitative approach. The subjects in this study were students of class X-1 Soko 1 High School in Tuban Regency, which amounted to 35 students. The selection of subjects was carried out by giving a profile adversity response questionnaire to 35 students in 1 class, namely class X-1 Soko 1 Public High School, Tuban District. From the ARP questionnaire selected as many as 3 students from 35 students namely 1 student climber category, 1 camper category student and 1 student quitter category. The data analysis technique used in this study is qualitative descriptive data analysis. Qualitative Tests are used to analyze test results and student interviews. Qualitative analysis carried out four activities simultaneously, namely: 1) reduction; 2) presentation; 3) triangulation, and 4) conclusion. The results of the analysis show that each subject is different in solving geometry problems.